(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
Sarf (morphology) is the science that studies the rules governing how the structure of words changes in order to convey specific meanings. Within this field, terms such as sarf, tasrif (inflection), and ishtiqaq (derivation) are used. The science of sarf primarily deals with nouns and verbs. The subject matter of sarf is Arabic words and how they change form to express meaning. It also examines transformations involving weak letters and similar linguistic phenomena. According to historical narrations, the first person to address this science was ‘Ali ibn Abi Talib. Some sources also mention Mu’adh ibn al-Harra as one of the earliest founders of the science of sarf.